Comprehensive analysis of lipids in biological systems by liquid chromatography-mass spectrometry - Cajka, Tomas; Fiehn, Oliver (TrAC, Trends in analytical chemistry (Regular ed.), 2014)
•State of the art in LC-MS-based lipidomics.•Sample extraction, separation, ionization and detection in LC-MS-based lipidomics.•Data processing, lipid identification/quantification, quality control in lipidomics.•Highlights of recent lipidomics studies. Liquid chromatography-mass spectrometry (LC-MS)-based lipidomics has undergone dramatic developments over the past decade. This review focuses on state of the art in LC-MS-based lipidomics, covering all the steps of global lipidomic profiling. By reviewing 185 original papers and application notes, we can conclude that current advanced LC-MS-based lipidomics methods involve: (1)lipid extraction schemes using chloroform/MeOH or methyl tert-butyl ether (MTBE)/MeOH, both with addition of internal standards covering each lipid class;(2)LC separation of lipids using short microbore C18 or C8 columns with sub-2-µm or 2.6–2.8-µm (fused-core) particle size with analysis time <30 min;(3)electrospray ionization in positive- and negative-ion modes with full spectra acquisition using high-resolution MS with capability to MS/MS. Phospholipids (phosphatidylcholines, phosphatidylethanolamines, phosphatidylinositols, phosphatidylserines, phosphatidylglycerols) followed by sphingomyelins, di- and tri-acylglycerols, and ceramides were the most frequently targeted lipid species.